Spinal pain syndromes among video game players - Korpak, Klaudia; Bac, Aneta; Ścisłowska-Czarnecka, Anna (Health Promotion & Physical Activity, 2020)
Aim of the study: The purpose of this study was to assess the occurrence of spinal pain syndromes among video game players. Material and methods: 550 persons took part in the survey, including 494 (89.8%) men and 56 (10.2%) women playing video games. The study was conducted using an online questionnaire created using Google Forms. The questionnaire contained 27 questions, including questions about time spent in a sitting position, the occurrence of spinal pain, ways of dealing with pain, and knowledge of the principles of spinal pain prophylaxis. Results: 70% of respondents play on the computer seven days a week, about 3-4 hours a day. Half of the surveyed players devoted one to two hours a day to physical exercise, one-third of the study subjects less than an hour, while every third video game player performed physical activity 3-4 times a week. When pain comes, almost 70% of respondents wait for it to subside, every fourth person treats themselves and the rest seeks help of a doctor or physiotherapist. Conclusions: There was no correlation between the number of years spent on playing video games and the occurrence of spinal pain as well as between the daily number of hours spent on playing video games and the occurrence of spinal pain.